Body Surveillance on Instagram: Examining the Role of Selfie Feedback Investment in Young Adult Women’s Body Image Concerns - Butkowski, Chelsea P.; Dixon, Travis L.; Weeks, Kristopher (Sex roles, 2019)
Selfies are self-taken self-portrait photographs captured with mobile phones, and they are among the most common forms of self-expression on the photo-based social network Instagram. Selfies display their subject’s face or body to social media followers and friends, making them particularly appearance-oriented images. As with other social networks such as Facebook and Twitter, Instagram posts garner feedback in the form of “ likes” and comments from online audiences. When applied to selfies, such feedback can be interpreted as aggregated evaluations of their subject’s physical appearance. We employ objectification theory to explore how value placed on selfie feedback among young women relates to markers of body image disturbance, including body dissatisfaction, drive for thinness, and bulimia action tendencies. We conducted an online survey of 177 English-speaking young adult (18–30 years-old) female Instagram users who were recruited through MTurk and who post selfies to examine the relationship between investment in selfie feedback and body image disturbance. We found that women who reported higher investment in selfie feedback were more likely to express body dissatisfaction and drive for thinness through the indirect influence of body surveillance, but this effect did not extend to bulimic tendencies. Our findings suggest that young adult female Instagram users who value audience responses to their selfies are more likely to exhibit disordered eating attitudes and intentions.